2023
DOI: 10.1038/s41431-023-01368-y
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the phenotypic spectrum of NAA10-related neurodevelopmental syndrome and NAA15-related neurodevelopmental syndrome

Abstract: Amino-terminal (Nt-) acetylation (NTA) is a common protein modification, affecting 80% of cytosolic proteins in humans. The human essential gene, NAA10, encodes for the enzyme NAA10, which is the catalytic subunit in the N-terminal acetyltransferase A (NatA) complex, also including the accessory protein, NAA15. The full spectrum of human genetic variation in this pathway is currently unknown. Here we reveal the genetic landscape of variation in NAA10 and NAA15 in humans. Through a genotype-first approach, one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 49 publications
1
55
1
Order By: Relevance
“…Table 5 compares the prevalence of CVI, myopia, astigmatism, strabismus, nystagmus, and hyperopia in our cohort to 106 previously reported cases, for a total of 173 individuals including those reported in this paper. Our cohort had significant overlap with the cohort reported previously 7 . However, the 37 probands from this paper who were not in our cohort were analyzed separately as seen in Table 5 .…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…Table 5 compares the prevalence of CVI, myopia, astigmatism, strabismus, nystagmus, and hyperopia in our cohort to 106 previously reported cases, for a total of 173 individuals including those reported in this paper. Our cohort had significant overlap with the cohort reported previously 7 . However, the 37 probands from this paper who were not in our cohort were analyzed separately as seen in Table 5 .…”
Section: Resultsmentioning
confidence: 65%
“…Previous literature suggests that NAA10 individuals present with more severe phenotypes than NAA15 individuals 7 . In terms of the ophthalmic phenotypes, we found no significant differences between NAA10 and NAA15 presentations.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Besides, the authors further perform the same analysis based on the different variant types in PHIP cohort to investigate whether we can distinguish patients based on the mutation types (Figure 6). Moreover, Lyon et al utilized GestaltMatcher to show that the patients with NAA10 ‐related neurodevelopmental syndrome and NAA15 ‐related neurodevelopmental syndrome shared a similar facial phenotype (Lyon et al, 2023). The tSNE plot in Figure 7 showed that the patients with NAA10 and NAA15 are similar and did not distribute in two clusters.…”
Section: Facial Phenotype Descriptors Delineate Facial Gestalt Of Dis...mentioning
confidence: 99%
“…It means that NAA10 and NAA15 patients presented a similar facial phenotype based on the GestaltMatcher analysis. This figure was published in the original paper (Lyon et al, 2023) as supplementary figs. 7 and 8.…”
Section: Facial Phenotype Descriptors Delineate Facial Gestalt Of Dis...mentioning
confidence: 99%